"Reparar la nación", discursos históricos y responsabilidades nacionalistas en Paraguay - Brezzo, Liliana M. (El Colegio de México, A.C., 2010)
This work analyzes the influence of nationalism in Paraguay's historical literature from 1897 to the centenary of its independence. It puts forward the essential ideas in published works and establishes a preliminary classification of their authors within Paraguayan historiography. Besides, the article proposes a series of reflections on the levels and processes of social historical awareness, accounting for several traits of Paraguayan  historical culture  and of historians  as some of the actors who produce this culture.